From gut to brain: exploring the impact of microbiota, dysbiosis, and neuroinflammation in neurodegenerative disorders - A. Deevan Paul; Harsini Natarajan (Future Journal of Pharmaceutical Sciences)
Abstract Neurodegenerative disorders, a group of diseases such as Alzheimer’s and Parkinson’s diseases, are identified by gradual memory and motor impairment, thus, seriously affecting aging populations. New research brings a paradigm shift in the pathogenesis of these conditions by identifying gut microbiota as a fundamental factor owing to dysbiosis through microbiota-induced neuroinflammation. Besides, the gut microbiome, referred to as dysbiosis, is exclusively responsible for activating the immune system thereby causing neuroinflammation, something that leads to breakdown of the blood–brain barrier and accumulation of toxic protein aggregates, such as amyloid-beta and alpha-synuclein. The gut-brain axis stays in the way of the advancement of such diseases, provided it allows for the necessary biochemical and immunity links. Microbial short-chain fatty acids (SCFA) and other metabolic by-products that are produced by these microbes either increase or decrease the stability of the central nervous system, while reduced SCFA production caused by dysbiosis, however, brings about neuroinflammation. From this perspective, the microbiota-gut-brain connection serves as a novel source for innovation in disease cure, including probiotics, prebiotics, dietary modifications, as well as the microbiota fecal transplant, restoring the microbial balance and thus, alleviating the disease progression. This examination establishes the current role of the microbiota in neurodegeneration and potential microbiome-focused treatments for neuroprotection.